1998
DOI: 10.1063/1.122249
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of temperature dependent photoluminescence line shapes in InGaN

Abstract: Infrared to vacuum-ultraviolet ellipsometry and optical Hall-effect study of free-charge carrier parameters in Mgdoped InN J. Appl. Phys. 113, 013502 (2013) Nanomechanical and optical properties of highly a-axis oriented AlN films Appl. Phys. Lett. 101, 254102 (2012) 2.8μm emission from type-I quantum wells grown on InAsxP1−x/InP metamorphic graded buffers Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(48 citation statements)
references
References 19 publications
4
43
0
1
Order By: Relevance
“…33,36,37 The degradation of PL efficiency at low N concentration in III-V semiconductor materials has been reported by several research groups. 12,42,43 Buyanova et al, for example, 43 observed similar nonradiative recombination channels, with activation energy of 50 meV, in the GaAsN/GaAs system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33,36,37 The degradation of PL efficiency at low N concentration in III-V semiconductor materials has been reported by several research groups. 12,42,43 Buyanova et al, for example, 43 observed similar nonradiative recombination channels, with activation energy of 50 meV, in the GaAsN/GaAs system.…”
Section: Resultsmentioning
confidence: 99%
“…This result agrees qualitatively with recently published studies; where no correlation was established between the thermal activation energy of nonradiative traps and the band-gap difference of QW and barrier materials. 33,[35][36][37] In this case, two hypotheses are considered to explain the quenching mechanism of the PL intensity for TϾ80 K: ͑i͒ the quenching is related to the escape of only one type of carrier ͑electrons or holes͒ from the QW to the barrier 31,33 and ͑ii͒ the quenching is related to the presence of defect states in the semiconductor structure. 33,36,37 In the first hypothesis, the activation energy, E a , would be given by the band offsets in the conduction or valence band.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that the localization effects arising from spatially inhomogeneous indium distribution played an important role for the spontaneous emission from InGaN/GaN quantum-well structures. [3][4][5][6][7][8][9][10] In particular, the localized exitons in the In-rich region acting as quantum dots were suggested to be responsible for the highefficiency radiative recombination. [8][9][10] However, the involvement of the localized states in the processes of carrier capture and recombination in InGaN/GaN LEDs with a multiple-quantum-well (MQW) active ( mesas with an area of 300 ϫ 300 m 2 , using an inductively coupled, plasma-etching system.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] In contrast to optical emitters based on conventional III-V semiconductors, InGaN-based light-emitting diodes (LEDs) show very high emission efficiency despite the existence of a high density of microstructural defects. 2 Understanding the origins of the high quantum efficiency of the LEDs is of high interest, not only from the viewpoint of material physics, but also in optimizing practical device design and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, at low temperatures, energy dependent radiative decay times for InGaN/GaN QWs are quoted [15][16][17][18] to be $10 s of nanoseconds compared with exciton decay times in GaAs/AlGaAs QWs $100 s of picoseconds. 19 It is widely accepted 18,[20][21][22][23][24] that the carrier localisation can, to a large extent, overcome non-radiative recombination associated with defects. However, the role of carrier localisation 25,26 in the process responsible for efficiency reduction at high carrier densities, the so-called efficiency droop, 27,28 is still the subject of extensive discussion.…”
Section: à2mentioning
confidence: 99%